Glycemic Effects and Safety of L-Glutamine Supplementation with or without Sitagliptin in Type 2 Diabetes Patients—A Randomized Study - Samocha-Bonet, Dorit; Chisholm, Donald J.; Gribble, Fiona M.; Coster, Adelle C. F.; Carpenter, Kevin H.; Jones, Graham R. D.; Holst, Jens J.; Greenfield, Jerry R. (PLOS ONE, 2014)
Background and Aims L-glutamine is an efficacious glucagon-like peptide (GLP)-1 secretagogue in vitro. When administered with a meal, glutamine increases GLP-1 and insulin excursions and reduces postprandial glycaemia in type 2 diabetes patients. The aim of the study was to assess the efficacy and safety of daily glutamine supplementation with or without the dipeptidyl peptidase (DPP)-4 inhibitor sitagliptin in well-controlled type 2 diabetes patients. Methods Type 2 diabetes patients treated with metformin (n = 13, 9 men) with baseline glycated hemoglobin (HbA1c) 7.1±0.3% (54±4 mmol/mol) received glutamine (15 g bd)+ sitagliptin (100 mg/d) or glutamine (15 g bd) + placebo for 4 weeks in a randomized crossover study. Results HbA1c (P = 0.007) and fructosamine (P = 0.02) decreased modestly, without significant time-treatment interactions (both P = 0.4). Blood urea increased (P<0.001) without a significant time-treatment interaction (P = 0.8), but creatinine and estimated glomerular filtration rate (eGFR) were unchanged (P≥0.5). Red blood cells, hemoglobin, hematocrit, and albumin modestly decreased (P≤0.02), without significant time-treatment interactions (P≥0.4). Body weight and plasma electrolytes remained unchanged (P≥0.2). Conclusions Daily oral supplementation of glutamine with or without sitagliptin for 4 weeks decreased glycaemia in well-controlled type 2 diabetes patients, but was also associated with mild plasma volume expansion. Trial Registration ClincalTrials.gov NCT00673894